2018
DOI: 10.1152/ajplung.00447.2017
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of the leptin receptor in myeloid cells impairs pulmonary clearance ofStreptococcus pneumoniaeand alveolar macrophage bactericidal function

Abstract: Leptin is a pleiotropic hormone produced by white adipose tissue that regulates appetite and many physiological functions, including the immune response to infection. Genetic leptin deficiency in humans and mice impairs host defenses against respiratory tract infections. Since leptin deficiency is associated with obesity and other metabolic abnormalities, we generated mice that lack the leptin receptor (LepRb) in cells of the myeloid linage (LysM-LepRb-KO) to evaluate its impact in lean metabolically normal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 50 publications
0
29
1
Order By: Relevance
“…Dock 7m also regulates the actin cytoskeleton, which is critical for phagosome maturation (36, 37). Mancuso et al (38) recently showed using leptin-receptor-deficient alveolar macrophages that leptin positively regulates Streptococcus pneumoniae clearance. This finding is consistent with the differential leptin response we observed between Gram-positive and Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Dock 7m also regulates the actin cytoskeleton, which is critical for phagosome maturation (36, 37). Mancuso et al (38) recently showed using leptin-receptor-deficient alveolar macrophages that leptin positively regulates Streptococcus pneumoniae clearance. This finding is consistent with the differential leptin response we observed between Gram-positive and Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, macrophage phagocytosis was impaired in leptin-deficient ob/ob mice [116]. Similarly, in leptin receptor-deficient db/db mice, peritoneal and alveolar macrophages showed defective phagocytosis and were skewed towards M2 polarization [117,118]. Collectively, the available data convincingly suggest that leptin can stimulate pro-inflammatory cytokine production in macrophages, hence potentially contributing to the acceleration of PDAC development by acting on pancreatic macrophages to drive ADM and early PanIN formation/transition in the context of obesity with accompanied hyperleptinemia.…”
Section: Pancreatic Stromal Macrophages In the Obese Statementioning
confidence: 99%
“…Obese Zucker (fa/fa) rats with a leptin receptor mutation, had reduced ability to clear the fungal infection Candida albicans in vivo, as measured by colonyforming units in lung, liver, spleen, heart, and kidney (75). Furthermore, mice with macrophage-specific deletion of the leptin receptor had impaired clearance of Streptococcus pneumoniae in the lungs and spleen (40). The same macrophage specific leptin receptor knockout mice also had elevated pulmonary IL-13 and TNF compared to WT mice 48 h after infection with S. pneumoniae (40).…”
Section: Macrophages and Monocytesmentioning
confidence: 99%
“…Furthermore, mice with macrophage-specific deletion of the leptin receptor had impaired clearance of Streptococcus pneumoniae in the lungs and spleen (40). The same macrophage specific leptin receptor knockout mice also had elevated pulmonary IL-13 and TNF compared to WT mice 48 h after infection with S. pneumoniae (40). Complementary in vitro studies of alveolar macrophages from macrophage specific leptin receptor knockout mice likewise showed decreased macrophage killing and phagocytosis (40).…”
Section: Macrophages and Monocytesmentioning
confidence: 99%